Epidemiology of Campylobacter infections among children of 0-24 months of age in South Africa - Amidou Samie; Resoketswe Charlotte Moropeng; Nicoline Fri Tanih; Rebecca Dillingham; Richard Guerrant; Pascal Obong Bessong (BMC, 2022)
Abstract Background Campylobacter spp. are one of the most frequent causes of diarrhoeal disease in humans throughout the world. This study aimed at determining the prevalence and the genotypic distribution of Campylobacter spp. and their association with diarrhoea and child growth in children of less than the age of two in the Limpopo Province of South Africa. Methods A total of 4280 diarrheal and non-diarrheal stool samples were collected on a monthly basis from children recruited at birth and followed up to 24 months. All stool samples were screened for the presence Campylobacter antigen using ELISA technique after which CAH 16S primer was used on the positive samples to confirm the presence of Campylobacter. Subsequently, the PCR positive samples were further characterised using species specific primers for Campylobacter jejuni and Campylobacter coli. Results Campylobacter antigen was detected in 564/4280 (13.2%). Campylobacter was more commonly found in diarrheal stools (20.4%) compared to non-diarrheal stools (12.4%) with a statistically significant difference (χ2 = 7.345; p = 0.006). Throughout the year there were two main peaks of Campylobacter infection one in December- January and the second peak in June. The prevalence of Campylobacter increased with the age of the children up to 11 months after which the prevalence decreased. Out of 564 positive ELISA samples, 257 (45.6%) were confirmed to have 16S rRNA gene for Campylobacter spp. Furthermore, C. jejuni was found to be more prevalent (232/257) than C. coli (25/257) with a prevalence of 90.3% and 9.7%, respectively. Both C. jejuni and C. coli were significantly associated with diarrhea with statistical values of (χ2 = 22.224; p < 0.001) and (χ2 = 81.682; p < 0.001) respectively. Sequences generated from the analysis of hip gene confirmed the PCR positives samples were C. jejuni positive. Conclusions This study has delineated a high prevalence of Campylobacter spp. in the study cohort. Moreover, C. jejuni was found to be more prevalent than C. coli both of which were associated with diarrhea. These findings are of clinical and epidemiological significance.